2011
DOI: 10.1177/0897190010388906
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Diseases in the Critically Ill Patients

Abstract: Infection is common in the critically ill and often results due to the severity of the patient's illness. Recent data suggest 51% of intensive care unit (ICU) patients are infected, and 71% receive antimicrobial therapy. Bacterial infection is the primary concern, although some fungal infections are opportunistic. Infection more than doubles the ICU mortality rate, and the costs associated with infection may be as high as 40% of total ICU expenditures. There are many contemporary antimicrobial resistance conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 52 publications
(95 reference statements)
1
23
0
Order By: Relevance
“…S. aureus is one of the main causes of bloodstream infections (3,4). Rapid identification of positive blood cultures is a prerequisite for timely targeted treatment of patients with sepsis (5-7).…”
mentioning
confidence: 99%
“…S. aureus is one of the main causes of bloodstream infections (3,4). Rapid identification of positive blood cultures is a prerequisite for timely targeted treatment of patients with sepsis (5-7).…”
mentioning
confidence: 99%
“…11 A meta-analysis found that the average attributable mortality to VAP is 32.5% in the ICU, 12 supported by another study 13 that found 33%. VAP increases the ICU and hospital length of stay, as well as the time the patient requires ventilatory support.…”
Section: Introductionmentioning
confidence: 92%
“…Critically ill patients are at a higher risk for serious infections caused by multi-drug resistant organisms (MDROs). Particularly in the intensive care unit (ICU), nosocomial infections lead to increased length of stay, greater morbidity and mortality rates, and need for post-hospitalization care [4]. Many factors contribute to the higher risks in the ICU including invasive devices, surgical or traumatic wounds, disruption of skin barriers and mucosa, and alterations in adaptive immune responses [4].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in the intensive care unit (ICU), nosocomial infections lead to increased length of stay, greater morbidity and mortality rates, and need for post-hospitalization care [4]. Many factors contribute to the higher risks in the ICU including invasive devices, surgical or traumatic wounds, disruption of skin barriers and mucosa, and alterations in adaptive immune responses [4]. Other risk factors include immunosuppression, longer hospital stay, multiple chronic conditions, recent invasive procedures, previous antibiotic use within 90 days, and even receiving care in the critical care units [1].…”
Section: Introductionmentioning
confidence: 99%